An Experimental Protocol for Femtosecond NIR/UV - XUV Pump-Probe Experiments with Free-Electron Lasers - Rolles, Daniel; Boll, Rebecca; Erk, Benjamin; Rompotis, Dimitrios; Manschwetus, Bastian (My University, 2018)
This protocol describes key steps in performing and analyzing femtosecond pump-probe experiments that combine a femtosecond optical laser with a free-electron laser. This includes methods to establish the spatial and temporal overlap between the optical and free-electron laser pulses during the experiment, as well as important aspects of the data analysis, such as corrections for arrival time jitter, which are necessary to obtain high-quality pump-probe data sets with the best possible temporal resolution. These methods are demonstrated for an exemplary experiment performed at the FLASH (Free-electron LASer Hamburg) free-electron laser in order to study ultrafast photochemistry in gas-phase molecules by means of velocity map ion imaging. However, most of the strategies are also applicable to similar pump-probe experiments using other targets or other experimental techniques.
Citation: Rolles, D., Boll, R., Erk, B., Rompotis, D., & Manschwetus, B. (2018). An Experimental Protocol for Femtosecond NIR/UV - XUV Pump-Probe Experiments with Free-Electron Lasers. JoVE (Journal of Visualized Experiments), (140), e57055–e57055. https://doi.org/10.3791/57055
Keywords: Chemistry; Pump-probe experiments; Femtosecond lasers; Free-electron lasers